Long-term effects of biochar on soil physical properties - Burrell, Leigh D.; Zehetner, Franz; Rampazzo, Nicola; Wimmer, Bernhard; Soja, Gerhard (Geoderma, 2016)
A growing body of research into the effects of biochar on soil physical characteristics suggests that it is most effective in coarse-textured soils. In this study, we set out to test this theory by comparing the effects of a woodchip biochar on a Chernozem, Cambisol and a coarse-textured Planosol in a pot experiment. We also compared the effect of different biochars on the Planosol, including woodchip biochar, straw biochar, and two vineyard-pruning biochars produced at different pyrolysis temperatures. Three characteristics were measured as indicators of good soil structure: bulk density, soil aggregate stability and plant available water. The woodchip biochar induced greater decreases in bulk density in the coarse textured Planosol than in the other soils. It also had a greater effect on soil aggregate stability in the Planosol than in the Cambisol, but had no effect on the Chernozem. Woodchip biochar had no effect on plant available water in any of the three soils. Straw biochar was the most effective at improving soil aggregate stability in the coarse-textured Planosol, with a 98% increase. Straw biochar also improved plant available water in the Planosol by 38% relative to the control, compared with 24% and 21% increases in the vineyard-pruning biochars, produced at 525°C and 400°C, respectively. Our study supports the theory that coarse-textured soils have the most to gain structurally from biochar amendments. We also show that straw biochar was the most effective at improving soil aggregate stability and plant available water in a coarse-textured Planosol. •Biochar permanently decreased bulk density in three agricultural soils.•Biochar improved soil aggregate stability in Planosol and Cambisol soils.•Biochars effect on soil aggregate stability correlated strongly with electrical conductivity.•Straw biochar improved plant available water in a Planosol soil by 38%.